Distribution of Argentine Flies (Cecidochares connexa Macquart) as a Biological Control Agent of Siamese Weeds (Chromolaena odorata L.) - Muin, Abdul; Santi, Idum Satia; Wahyud, Dicky; Manto, Agus (Tropical Plantation Journal, 2025)
This study aims to determine the level of attack and distribution of Argentine flies (Cecidochares connexa) as biological control agents against Siamese weed (Chromolaena odorata) in Gunungkidul Regency. The method used was a field survey in June–July 2024, with direct observation and sampling of host plants in four cardinal directions from the starting point of release (Wanagama I Forest). The parameters observed included the percentage of attacks, the number of puru, and puru holes per plant. The results showed that the highest attacks occurred in the Western region (72%), followed by the South (69%), the North (68%), and the East (49%). The average attack across the region reached 65%.  C. connexa has become widespread and established in the Gunungkidul area.